The Greek article : a functional grammar of o-items in the Greek New Testament with special emphasis on the Greek article - Peters, Ronald D. (Linguistic Biblical Studies, 2014)
In The Greek Article , Ronald D. Peters presents a grammar of the Greek article and relative pronoun, categorized as ὁ-items, which was formulated using the principles of Systemic-Functional Linguistics. This categorization stands in contrast to previous grammars, which have categorically associated the article with the demonstrative pronoun. Thus, the present work represents a significant paradigm shift in the study of the Greek article. Unlike previous approaches that have too often yielded internally inconsistent and contradictory rules of usage, this approach results in a description of the article's function that is uniform across all occurrences. Simultaneously simple and robust, this grammar promises to pay significant dividends for exegetes and translators of the Greek New Testament.